TrustMyCounsell: A Counselling Management Application for KKTM Sri Gading with Data Privacy Techniques - Quek, Sze Yang; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2025)
The COVID-19 pandemic highlighted the need for secure online counselling, as existing systems often lacked robust data protection, privacy, and PDPA compliance, eroding user trust. This study introduced TrustMyCounsell, a secure platform for KKTM Sri Gading, incorporating end-to-end encryption (E2EE) for private communications and data anonymization to protect personal information. Developed via agile methodology, key modules include user registration, session booking, journaling, homework tracking, and feedback. Comprehensive functional testing confirmed module reliability. Security testing validated E2EE and data anonymization's effectiveness in ensuring confidentiality. User Acceptance Testing (UAT) affirmed the platform's user-friendliness, its success in enhancing trust, and streamlining counselling workflows. TrustMyCounsell offers a user-friendly, secure platform, reducing data breach risks and fostering a confidential environment for users by implementing robust data protection. It aims to enhance trust and accessibility of counselling services.